A Systematic Review On The Effectiveness Of Using Smart Prevention System To Overcome Fire Disaster - Salim, Salman; Salman, Mohamad Amirul Haziq; Rosli, Muhammad Alif Akmal; Samsudin, Muhammad Isma Danish; Mohd Yusoff , Muhammad Khairul Fahmi (Multidisciplinary Applied Research and Innovation, 2020)
Automatic fire prevention systems are installed in large capacity buildings and residential areas where fire risk is high. So this paper discusses the effectiveness and capabilities of the fire prevention system in extinguishing fires in a short time at an early stage. However, there are some complaints from users that the system is not working correctly, the installation cost is too expensive, and the system design is not relevant nowadays. Therefore, from the complaints identified, we have conducted a study to issue a systematic survey to assess the public's understanding of the cost of installing this system in residential and building areas. A study was also conducted to identify the current work system to be used as a reference so that new upgraded systems can be released and examine the use of Arduino UNO in the current system. The previous studies through the Google Scholar platform, Science Direct, and official websites have related to the study were fine and shortlisted a total of 30 articles journals as references. Overall, this systematic review found some information to support where there are some shortcomings of the existing fire prevention system. This system needs to be upgraded to be more effective in dealing with fires in the future.